Effect of Using Air Guide Net in Front of the Condenser on the Performance of Automobile Air Conditioning System - Mahdi, Mahmoud Maustafa; Gaddoa, A. A. (Al-Khwarizmi Engineering Journal, 2019)
The work of this paper is an investigation to improve the condenser performance of the automobile air conditioning system by enhancing the air-side heat transfer from the condenser through the use of an air guide net installed in front of the condenser face which is basically an aluminum plate having a circular entrance shape for the air passage. The A/C system was examined under two types of test. The first test was conducted the air guide net, while the second was done with the air guide net. The performances of the A/C system under these tests were compared. For the second type of test, the experiment was carried out with three different size of air guide net, three different circular diameters (2, 3 and 3.5 cm) and a common air passage area. The effect of varying the size of the air guide net and its inclination angle was investigated. The experimental work included five inclination angles (0o, 5o, 10o, 15o and 20o). It was found that the presence of the air guide net caused an improvement in the performance of the A/C system for all sizes and inclination angles. In addition, the electrical energy consumed by the A/C system without the air guide net was calculated and compared to those obtained for the A/C system with the air guide net. The results manifested that the reduction of the power consumption was enhanced by operating the A/C system with the air guide net.